Defining Freedom: An Analysis of Freedom in Anthony Burgess’ “A Clockwork Orange” - Fajar Purnomo Adi (Universitas Pendidikan Indonesia (UPI), 2016)
This research investigates the issue of freedom in Anthony Burgess’ novel “A Clockwork Orange (1962). The aim of the research is to identify the way this novel define freedom. The research employs descriptive qualitative method in which the writer describes, interprets and analyses the text to answer the research question. This study uses the works of Anshari (2014) and Gallie (1956) on freedom in post-colonialism along with the works of Swenson (1948) and Dastagir (2007) on freedom in existentialism as the theoretical framework to analyse the data. The findings show that this novel defines freedom through the actions of the main character, Alex who is driven by two factors in three stages of freedom and also a question of freedom that repeated throughout the novel. Moreover, the research also finds that according to the novel, freedom is a treat that is specialized for humans and thus becomes the characteristics of being a human and differentiate humans with any other creature. When humans lose their freedom, they cannot choose and those who cannot choose cease to be humans.Keywords: Post-Colonialism, Existentialism, Freedom